Adaptasi lintas budaya mahasiswa di asrama mahasiswa nusantara (AMN) Surabaya: tinjauan teori Kim 2001 - Permatasari, Putri; febriyanti, syafrida Nurrachmi (Universitas Garut, 2025)
Abstract This research is motivated by the Nusantara Student Dormitory (AMN) scholarship program initiated by President Joko Widodo in 2022, which aims to foster intercultural interaction among students from 38 provinces across Indonesia. The diverse environment within the dormitory creates a potential for conflict, requiring AMN students to adapt to the variety of ethnicities, cultures, and backgrounds present in the community in order to sustain their two-year stay. This study aims to analyze and describe the process of intercultural adaptation experienced by AMN students during their time in the dormitory. This study uses a qualitative descriptive approach, this study involved ten informants consisting of alumni, active residents, and AMN student mentors who come from diverse cultural backgrounds. Data were collected through in-depth interviews as the primary source and document studies as secondary data. The analysis employs Kim’s (2001) Cross-Cultural Adaptation Theory to explore the dynamics of the adaptation process. The findings reveal that the intercultural adaptation process experienced by AMN students is both dynamic and complex. It begins with experiences of culture shock during intercultural communication—both verbal and nonverbal—followed by a phase of adjustment through continued cultural interaction, ultimately leading to changes in the students themselves. The adaptation process is not always smooth, as it often encounters barriers and resistance. Nevertheless, intercultural adaptation leads to a series of changes in AMN students, affecting their cognitive, affective, and behavioral aspects. The study also identifies a gap between the theoretical framework and the participants’ experiences: while Kim’s theory views adaptation as a long-term psychosocial process, the informants tended to interpret adaptation as the achievement of personal comfort or stability. Key Words: Intercultural communication; cross-cultural adaptation; asrama mahasiswa nusantara (AMN). Abstrak Penelitian ini dilatarbelakangi oleh program beasiswa pendidikan Asrama Mahasiswa Nusantara (AMN) yang diinisiasi oleh presiden Joko Widodo pada tahun 2022. Program ini bertujuan untuk mendorong interaksi lintas budaya di kalangan mahasiswa, dengan penerima beasiswa berasal dari 38 provinsi di Indonesia. Keberagaman ini berpotensi menimbulkan konflik, sehingga menuntut mahasiswa untuk beradaptasi dengan perbedaan suku, etnis dan budaya selama dua tahun tinggal di asrama. Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan proses adaptasi lintas budaya mahasiswa AMN selama tinggal di asrama. Penelitian ini menggunakan pendekatan deskriptif kualitatif, penelitian ini melibatkan sepuluh informan yang terdiri atas alumni, penghuni aktif, dan mentor mahasiswa AMN yang berasal dari latar belakang budaya yang beragam. Data dikumpulkan melalui wawancara mendalam sebagai sumber primer, serta studi dokumentasi sebagai data sekunder. Analisis penelitian menggunakan teori Cross-cultural adaptation oleh Kim (2001) untuk menelaaht dinamika proses adaptasi lintas budaya. Hasil penelitian menunjukkan bahwa proses adaptasi lintas budaya yang dialami mahasiswa AMN berjalan dinamis dan kompleks. Proses ini dimulai dari pengalaman gegar budaya dalam komunikasi antar budaya, baik secara verbal maupun non verbal, dilanjutkan dengan penyesuaian melalui komunikasi antar budaya, hingga perubahan yang terjadi pada diri mahasiswa. Proses adaptasi tidak selalu berjalan mulus dan kerap menghadapi hambatan serta penolakan. Namun demikian, adaptasi lintas budaya membawa perubahan signifikan pada aspek kognitif, afektif dan perilaku mahasiswa. Penelitian ini juga menemukan adanya kesenjangan dengan teori, dimana informan memaknai adaptasi sebagai titik kenyamanan pribadi, bukan sebagai proses psikososial yang berlangsung jangka panjang sebagaimana yang di jelaskan dalam teori Kim. . Kata-kata kunci: Komunikasi antar budaya; adaptasi lintas budaya; asrama mahasiswa nusantara (AMN).